Nucleosome binding and histone methyltransferase activity of Drosophila PRC2. - Nekrasov, M.; Wild, B.; Müller, J. (EMBO Reports, 2005)
The Drosophila Polycomb group protein E(z) is a histone methyltransferase (HMTase) that is essential for maintaining HOX gene silencing during development. E(z) exists in a multiprotein complex called Polycomb repressive complex 2 (PRC2) that also contains Su(z)12, Esc and Nurf55. Reconstituted recombinant PRC2 methylates nucleosomes in vitro, but recombinant E(z) on its own shows only poor HMTase activity on nucleosomes. Here, we investigate the function of the PRC2 subunits. We show that PRC2 binds to nucleosomes in vitro but that individual PRC2 subunits alone do not bind to nucleosomes. By analysing PRC2 subcomplexes, we show that Su(z)12-Nurf55 is the minimal nucleosome-binding module of PRC2 and that Esc contributes to high-affinity binding of PRC2 nucleosomes. We find that nucleosome binding of PRC2 is not sufficient for histone methylation and that only complexes that contain Esc protein show robust HMTase activity. These observations suggest that different subunits provide mechanistically distinct functions within the PRC2 HMTase: the nucleosome-binding subunits Su(z)12 and Nurf55 anchor the E(z) enzyme on chromatin substrates, whereas Esc is needed to boost enzymatic activity.